Measuring phantom borders: the case of Czech/Czechoslovakian electoral geography - Šimon, Martin (ERDKUNDE, 2015)
The article focuses on Czech/German ethnic boundary from former interwar Czechoslovakia and its persistence (or transience) in electoral behaviour in selected post-1989 elections. In the analytical part of the article links between populations in regions and electoral results is discussed in order ‘extract’ phantom borders. The analysis draws on both recent GIS data on historical spatial units and historical electoral data to explore the concept of phantom borders. The focus is on phantom borders that can be observed in electoral data and cannot be identified in contemporary socio-economic data or structures and thus reflect institutional (in)stabilities of regional institutions as reflected in electoral behaviour. In conclusion, the article notes some methodological problems connected with the delimitation and visualisation of phantom borders in electoral maps.